Materii prime pentru încălţăminte : metode şi mijloace de testare a calităţii - Dragomir, Alina (Performantica, 2009)
"The book, namely Materials for Footwear Manufacturing presents the methods and equipments for testing and it brings together information about raw and auxiliary materials for footwear, as well information about available standards for quality. This publication could be a working instrument for technicians, researchers, teachers and students involved in footwear and leather goods industry."--Anotace od dodavatele
Keywords: obuvnické materiály; zkoušení materiálů; material testing; shoe materials; příručky; handbooks, manuals, etc